A metallographic case study of formicary corrosion in heat exchanger copper tubes. (April 2020) - Lachowicz, Marzena Małgorzata
Highlights: The formicary corrosion occurring on the inner surface of the tubes made of Cu-DHP has been described. The nature of the occurring changes with the use of light microscopy and SEM/EDS techniques has been illustrated. The important role of surface condition caused by technological processes and non-metallic inclusions on the initiation of corrosive changes has been shown. Abstract: This paper presents the results of tests for corrosion damage that occurred on the inner surface of copper tubes of a shell and tube heat exchanger. A typical image was observed for corrosion caused by the presence of organic decomposition products on the copper surface, leading to the formation of carboxylic acids. Light microscopy and SEM was used to describe the nature of the ant-nest corrosion. It has been observed that the orientation of the formed tunnels can be related to their movement along the grain boundaries. The research also focused on the important role of the surface condition caused by technological processes and non-metallic inclusions on the initiation of corrosive features.